EDUCATIONAL OBJECTIVES BASED ON VALUES OF REVELATION - Khambali Khambali (TA'DIB: JURNAL PENDIDIKAN ISLAM, 2020)
The purpose of this research is to try to explore and describe the goals of education in Islam inductively by looking at the arguments of naqli that already exist in the al-Qur'an and al-Hadith, as well as integrating them in the context of the needs of society in general in education, so that the goal is expected. education in Islam can be applied to contemporary discourse and reality. The research design used is literature research with a revelatory approach to a number of verses from the Al-Qur'an about educational purposes, and interpretive books as primary data sources and journals and scientific writings as secondary data. The commentaries studied were Tafsir Al-Qur'an Al-'Adzim (Tafsir Ibn Katsir), Tafsir Al-Maraghi, and others. The commandment to make preparations, to provide everything including with the right determination and enthusiasm. The purpose of education is as guidance so that humans do not perish with the hardships they experience. Al-Qur'an is an information for every human being, guidance, explanation, teaching and warning for people who have faith. The command to manifest respect and affection for fellow human beings shows that a servant must always prostrate and repent to Allah SWT, and remind humans to always please others. Keywords: Educational Objectives; Revelation Values.  Abstrak  Tujuan dari penelitian ini adalah berusaha menggali dan mendeskripsikan tujuan pendidikan dalam Islam secara induktif dengan melihat dalil-dalil naqli yang sudah ada dalam al-Qur’an maupun al-Hadits, juga memadukannya dalam konteks kebutuhan dari masyarakat secara umum dalam pendidikan, sehingga diharapkan tujuan pendidikan dalam Islam dapat diaplikasikan pada wacana dan realita kekinian.  Desain penelitian yang digunakan adalah penelitian kepustakaan dengan pendekatan kewahyuan terhadap sejumlah ayat Al-Qur’an tentang tujuan pendidikan, dan kitab-kitab tafsir sebagai sumber data primer dan jurnal serta tulisan ilmiah sebagai data sekunder.  Kitab tafsir yang dikaji adalah Tafsir Al-Qur’an Al-‘Adzim (Tafsir Ibnu Katsir), Tafsir Al-Maraghi, dan lainnya. Perintah untuk melakukan persiapan, menyediakan segala sesuatunya termasuk dengan tekad dan semangat yang benar. Tujuan pendidikan adalah sebagai bimbingan agar manusia tidak binasa dengan kesusahan yang dialaminya. Al-Qur’an adalah penerangan bagi setiap manusia, petunjuk, penjelasan, pengajaran dan peringatan bagi orang-orang yang bertaqwa. Perintah untuk mewujudkan rasa hormat dan rasa kasih sayang sesama manusia, menunjukkan bahwa seorang hamba haruslah selalu sujud dan taubat kepada Allah Swt, serta mengingatkan kepada manusia untuk selalu menyenangkan orang lain. Kata Kunci: Tujuan Pendidikan; Nilai-nilai Kewahyuan.